1999
DOI: 10.1093/jac/44.1.85
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial treatment of an experimental otitis media caused by a β-lactamase positive isolate of Haemophilus influenzae

Abstract: A gerbil model of otitis media induced by a beta-lactamase producing and non-serotypeable isolate of Haemophilus influenzae was used to assess the in-vivo efficacy of co-amoxiclav and cefuroxime at low (5 mg/kg) and high (20 mg/kg) doses. The MIC of the antibiotics tested against the pathogen was 1 mg/L (1/0.5 mg/L for co-amoxiclav). The organism was inoculated (+/-10(6) cfu) by transbullar challenge directly in the middle ear and antibiotic treatment was commenced 2 h post-inoculation and continued at 8 h int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…For these reasons, we have studied the effect of delayed antibiotic administration on the course of experimental AOM caused by both penicillinsensitive and -resistant S. pneumoniae strains. This model has been very useful for evaluating antibiotic treatment either for AOM or for otitis media with effusion (OME) (1,2,4,21,23,25). Most of these experimental models have shown that many organisms inoculated into the middle ear (ME) are cleared by antibiotics active in vitro, but in most published studies the antibiotics were administered very early.…”
mentioning
confidence: 99%
“…For these reasons, we have studied the effect of delayed antibiotic administration on the course of experimental AOM caused by both penicillinsensitive and -resistant S. pneumoniae strains. This model has been very useful for evaluating antibiotic treatment either for AOM or for otitis media with effusion (OME) (1,2,4,21,23,25). Most of these experimental models have shown that many organisms inoculated into the middle ear (ME) are cleared by antibiotics active in vitro, but in most published studies the antibiotics were administered very early.…”
mentioning
confidence: 99%
“…This strain was the same as the strain previously used in our single H. influenzae otitis media model [19].…”
mentioning
confidence: 99%
“…In the previously reported model [6], the increase in amoxicillin/clavulanic acid ME concentrations by the increased inflammation induced by S. pneumoniae allowed the ␤-lactam to eradicate H. influenzae even at low doses. In this AOM model, amoxicillin/clavulanic acid administered at 1.5 mg/kg (referred as amoxicillin) achieved ME concentrations higher than those obtained after the administration of doses three times higher (5 mg/kg) in an OME model (1.17 g/ml versus 0.95 g/ml with 45% versus 10% penetration in relation to serum concentrations) [7]. This was not the case for the macrolide, since the penetration of erythromycin into the ME in this AOM (mixed) model was not higher than the one achieved in an OME model caused by H. influenzae alone (40.6% versus 43.6%) (unpublished data).…”
Section: Discussionmentioning
confidence: 85%
“…Beta-lactam antibiotic concentrations in ME fluid were lower in OME than in AOM, probably due to the lower inflammatory reaction associated with OME [6]. Doses of amoxicillin/clavulanic acid (A/C) that achieve ME concentrations in OME [7] that are similar to those obtained in humans after standard doses [8] are effective in eradicating H. influenzae (with an MIC of 1 mg/l, a value similar to the MIC50/MIC90 in Spain), but eradication did not occur with lower doses [7]. In contrast, these lower doses in a mixed (S. pneumoniae plus H. influenzae) AOM model were able to eradicate both organisms due to the higher antibiotic concentration in the ME fluid, probably due to a greater inflammatory reaction [6].…”
Section: Introductionmentioning
confidence: 99%